Evaluation of luteinizing hormone-releasing hormone antagonistic activity in vitro. - Csernus, V J (1992)
Antagonistic analogues of luteinizing hormone-releasing hormone (LHRH) belong to a class of compounds that can be utilized for treatment of some hormone-dependent cancers and gynecologic disorders. Recently, we synthesized and tested a large number of LHRH analogues for LHRH antagonistic activity in the dispersed pituitary cell superfusion system. This fast, reliable, and dynamic system made it possible for us not only to evaluate the relative amounts of an analogue required for suppression of the LH-releasing activity of exogenous LHRH but also provided quantitative data on dynamic interactions between the LHRH analogue, LHRH receptors, and LH secretion. Three experimental paradigms were used: (i) LHRH responses after preincubation with the antagonist, (ii) pulsatile, simultaneous infusion of LHRH and the antagonistic analogue, and (iii) effects of the analogues on ongoing, continuous LH secretion induced by prolonged stimulation with LHRH. From the data obtained, we conclude that (i) the suppression of the LHRH-induced LH release was more effective and longer lasting when the cells were preincubated with the antagonistic analogues before the LHRH stimulation than in the case of simultaneous exposure; (ii) not only the potency but also the time of onset and the duration of the LH release-suppressing activity varied according to the different peptides used, resulting in different shapes of response curves; and (iii) from the accurate data obtained in this dynamic system, quantitative parameters of the in vivo interactions between the antagonists and LHRH on the LHRH receptor can be calculated.